Clock Tree Generation: The Implementation Of Zero Skew Clock Net Router - Mohammad, Mohammad Azam (2006)
In this thesis, a Zero Skew Clock Routing Methodology is presented. This methodology was developed to help design team speed up their clock tree generation process.